A Theory of Patent Portfolios - Jay Pil Choi; Heiko Gerlach (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper develops a theory of patent portfolios in which firms accumulate an enormous amount of related patents in diverse technology fields such that it becomes impractical to develop a new product that with certainty does not inadvertently infringe on other firms' patent portfolios. We investigate how litigation incentives for the holders of patent portfolios impact the incentives to introduce new products and draw welfare implications. We also consider a patent portfolio acquisition game in which a third party's patent portfolio is up for sale.
Keywords: D43; L13; O30; 330; patent portfolios; patent litigation; practicing and non-practicing entities; patent troll